Compulsory service in the context of Islam, law and civil policy - Ahmad, Rusniah (Universiti Utara Malaysia, 2004)
Compulsory service is not an alien concept in an era of individualism and freedom. It is a concept of compromising with modern assertions of culture and life. In an era where educating the young becomes a commitment for the community, practical and physical training form a part of that process. Apart from that, the ailments of modernization have been responsible for curtailing the advancement of youth in many areas of knowledge and thinking. Therefore the need for discipline spells out more than just going to school and completing that similar cycle of defining what it means to be young and at the same time belligerence. In legal term compulsory service may not be popular with the notion of liberty and individual freedom but turns into a national responsibility to be understood and fulfilled by all Malaysians. Thus Article 6 of the federal constitution permits Parliament to enact a law that provides for compulsory service for Malaysians. In fact this idea is gradually gaining ground in other parts of the world which include surprisingly the United States. Compulsory service is also part of an efJort to harness patriotic spirit with the creation of more opportunities for people to volunteer or sewe the military. A significant impact that can be seen from this policy is that people will have an opportunity to view military training in a different perspective as not only part of physical training but an important part of the process of educating the young.